(untitled) (Revista de Ciências Agroveterinárias, 2019)
Due to a lack of technical-scientific information about the effect of the retained node number on the interception of the solar radiation of the nodes and its effect on the fertility of nodes, this work aims to evaluate the effect of the increased number of nodes of the grapevine Cabernet Franc in relation to the interception of the photosynthetically active composition and its effect on the node fertility in high altitude region of Santa Catarina State. This experiment was conducted during the 2016/2017 harvest in a commercial vineyard located in the city of São Joaquim. Cabernet Franc plants grafted on the ’Paulsen 1103’ rootstock were used. The treatments consisted of four different levels of retained node numbers: 15, 30, 50, and 75 nodes per plant. The experimental design was a randomized block design with four blocks and five plants per plot. The data were submitted to analysis of variance (ANOVA) and compared by the Tukey test with a 5% probability of error. The results of this study evidenced the importance of the interception of the photosynthetically active radiation in the nodes fertility, observing the reduction of the nodes fertility in situations of reduction of the interception of the photosynthetically active radiation, in this case, caused by the increase of the number of nodes, which resulted in a higher shoot number and branches, resulting in a denser canopy, and consequently reducing the interception of the photosynthetically active radiation that reaches the grape nodes, being this effect more pronounced in the buds located at the basal position of the branch.